Inverse Processing of Undefined Complex Shape Parts from Structural High Alloyed Tool Steel. (19th February 2014) - Monkova, Katarina; Monka, Peter; Hloch, Sergej
Abstract : The paper deals with the process of 3D digitization as a tool for increasing production efficiency of complex shaped parts. Utilizes the concept of reverse engineering and new the model of NC program generation STEP-NC, for the of templates production for winding the stator coil of electromotors that is for electric household appliances. The manual production of prototype was substituted by manufacturing with NC machines. A 3D scanner was used for data digitizing, CAD/CAM system Pro/Engineering was used for NC program generation, and 3D measuring equipment was used for verification of new produced parts. The company estimated that only due to the implementation of STEP NC standard into production process it was allowed to read the 3D geometry of the product without problems. It helps the workshop to shorten the time needed for part production by about 30%.